Differences in Anxiety Levels of Health Workers before and after Covid-19 Vaccination - Suprayitno, Emdat; Hidayat, Syaifurrahman (Griya Eka Sejahtera, 2023)
Background: The rapid spread of the disease can cause anxiety because it is crucial for health workers to get the Covid-19 vaccine to boost the immune system at work. This study aimed to determine differences in anxiety levels before and after receiving the first dose of the Covid-19 vaccine among medical personnel.Methods: This study used a retrospective study with a comparative method with a cross-sectional design and primary data collection through a questionnaire. Results of statistical analysis using Wilcoxon test.Results: The results showed that before being given the first dose of the vaccine, the number of health workers who experienced severe anxiety was 32 (72.8%). Moderate anxiety was 12 people (27.3%). after being given the first dose of the vaccine, the number of health workers who experienced severe anxiety was as many as 14 people (31.8%), moderate anxiety as many as 24 people (54.6%) and mild anxiety as many as six people (13.6). The Wilcoxon test showed a P-value = 0.000.Conclusion: Differences in the anxiety levels of health workers before and after being given the first dose of the Covid-19 vaccine. Presenting the first dose of vaccine can reduce anxiety in health workers